Association between sagittal plane posture and quality of life in older people: a systematic review - Gasparotto, Lívia Pimenta Renó; Falsarella, Gláucia Regina; Coimbra, Arlete Maria Valente (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
Introduction: Changes in postural pattern during aging establish the body structural modifications that can compromise quality of life. The relationship between postural change and quality of life seems hardly mentioned among researches. Objective: The purpose of the article is to check on the subject’s analyses, what are the possible associations should be highlighted in the preventive scope of the elderly with postural dysfunctions. Method: We used systematic review based on Pubmed and Lilacs by descriptors related to posture words and quality of life. The search was focused on articles published between 2005-2015. To analyze the quality and combination of data applied the STROBE checklist. Results: It identified 11 studies from which hyperkyphosis posture and lumbar adjustment were negatively associated with quality of life components. Conclusion: There was divergence in the direction of the association between lumbar concavity and quality of life. Although these observations contribute to the direction of preventive and corrective practices posture in aging, there is a need for more studies using mainly similar methodologies and homogeneous groups.